Numerical study and structural optimization of mid-and-low temperature solar absorber/reactor for methanol decomposition. (5th January 2023) - Dou, Lizhuang; Zhang, Yidian; Li, Xiao; Mu, Mingfei; Ding, Bin
Highlights: A multi-physics coupling numerical model of MLTSAR is established. The circumferential non-uniform heat flux has a slight effect on the MCR and STE. The MCR and STE of MSR is higher and lower than that of MD, respectively. A novel structure can enhance the MCR and STE by 1.47% and 1.49%, respectively. Abstract: Driving endothermic thermochemical reactions by employing concentrated solar thermal energy is a perspective method for efficient utilization of solar energy, and solar reactor is a key equipment for wider application. In this paper, a multi-physics coupling model of mid-and-low temperature solar absorber/reactor (MLTSAR) for methanol decomposition (MD) reaction is established. The thermochemical performance of MLTSAR and the influencing factors including solar radiation intensity and non-uniform solar heat flux in circumferential direction are studied. The non-uniform solar heat flux in circumferential direction has a slight effect on the methanol conversion rate (MCR) and solar thermochemical efficiency (STE) but it leads to the non-uniform temperature distribution of absorber/reactor. And then, the comparative study of the thermochemical characteristic between MD and methanol steam reforming (MSR) reaction indicates that the MCR of MSR is higher than that of MD, but the STE is lower than that of MD. The MLTSAR structure is optimized by changing the aperture width, to reduce the energy level difference between the concentrated solar heat and the chemical reaction. The results show that compared with the original MLTSAR, the MCR and STE of the novel MLTSAR can be enhanced by 1.47% and 1.49%, respectively, and the outlet temperature is reduced by 15.48 K under the typical working condition. This optimization scheme could guide the design of practical solar reactors.